The effectiveness of the balanced scorecard on strategy management processes: a case study in a Portuguese industrial company - Ferreira, A.; Rodrigues, J. (Global Advanced Research Journal of Management and Business Studies, 2013)
The Balanced Scorecard (BSC) has assumed a prominent role as a reference methodology for research purposes and as an internationally adopted corporate practice. However, it is difficult to assess the success of the BSC on financial performance. This study investigates the effectiveness of the BSC on the strategy management processes: translation of vision and strategy; communication and alignment of strategic objectives; planning, definition of milestones and alignmentwith initiatives; promotion of feedback and learning. The study adopts an exploratory and explanatory qualitative case study approach and focuses on a business unit of a large industrial company. The study describes a successful case of the adoption and use of the BSC methodology. The results demonstrate that the BSC improves strategy management processes and can be used to implement planned strategies and lead to the emergence of new initiatives and actions. The study identifies critical success factors that determine the effectiveness of the BSC on strategy management processes.